Early Peritoneal CC Chemokine Production Correlates with Divergent Inflammatory Phenotypes and Susceptibility to Experimental Arthritis in Mice - Cristiano Rossato; Layra Lucy Albuquerque; Iana Suly Santos Katz; Andrea Borrego; Wafa Hanna Koury Cabrera; Mônica Spadafora-Ferreira; Orlando Garcia Ribeiro; Nancy Starobinas; Olga Martinez Ibañez; Marcelo De Franco; José Ricardo Jensen (Journal of Immunology Research)
The inflammatory and autoimmune events preceding clinical symptoms in rheumatoid arthritis (RA) and other autoimmune diseases are difficult to study in human patients. Therefore, animal models that share immunologic and clinical features with human RA, such as pristane-induced arthritis (PIA), are valuable tools for assessing the primordial events related to arthritis susceptibility. PIA-resistant HIII and susceptible LIII mice were injected i.p. with pristane, and peritoneal lavage fluid was harvested in the early (7 days) and late (35 days) preclinical phases of PIA. Chemokine and cytokine levels were measured in lavage supernatant with ELISA, peritoneal inflammatory leukocytes were immunophenotyped by flow cytometry, and gene expression was determined by qRT-PCR. Leukocyte recruitment was quantitatively and qualitatively divergent in the peritoneum of HIII and LIII mice, with an early increase of CC chemokines (CCL2/CCL3/CCL5/CCL12/CCL22) in the susceptible LIII strain. Also, cytokines such as IL-12p40, IL-23, and IL-18 were elevated in LIII mice while IL-6 was increased in HIII animals. The results show that an early peritoneal CC chemokine response is an important feature of arthritis susceptibility and defines potential biomarkers in this model.